MITOS DAN RELASI KETIDAKSADARAN MASYARAKAT - Fajar W. Hermawan (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2016)
Most of the philosophers assert that every human effort to uncover the myth eventually would be trapped or bring out a new myth. Since the myth is important in order to form the structure of the human mind, then, it is interesting to discuss the analysis proposed by Roland Barthes. The contributions of Barthes, with his study of myth, at least would open a new horizon regarding the understanding, the structure, and the relations of the myth with the real world. Barthes’ efforts in analyzing the myths, especially the contemporary myths, might be taken to be different from what were done by the earlier experts. The studies of Barthes have developed the awarenessand the new horizon about things previously taken unimportant and trivial, especially in the context of the modern world.